Biological, chemical and toxicological perspectives on aerial and roots of Filago germanica (L.) huds: Functional approaches for novel phyto-pharmaceuticals. (January 2019) - Saleem, Hammad; Htar, Thet Thet; Naidu, Rakesh; Nawawi, Nurziana Sharmilla; Ahmad, Irshad; Ashraf, Muhammad; Ahemad, Nafees
Abstract: We investigated into the effects of methanol and dichloromethane extracts from aerial and roots of Filago germanica (L.) Huds (Astearaceae) on key enzymes (cholinesterases, α-glucosidase and urease), antioxidant capabilities, cytotoxic potential and secondary metabolomics profile. Total phenolic and flavonoids were determined by spectrophotometric technique and secondary metabolites composition by UHPLC-MS. Antioxidant activities were assessed employing free radical scavenging, ferric reducing power and phosphomolybdenum assays. The cell-toxicity was evaluated by MTT assay against breast (MCF-7, MDA-MB-231), cervix (CaSki) and prostate (DU-145) cancers. Overall, methanol extracts were found to have higher total bioactive contents and antioxidant potential. UHPLC-MS analysis revealed significant variation in the secondary metabolites in the methanol extracts. The most common derivatives belong to seven groups i.e. alkaloids, benzoic acids, flavones, flavonols, flavan-3-ols, terpenoids and saponins. The major polyphenolic compounds were found to be kampferol, robinin, luteolin, ferulic acid, benzoic acid and salicylic acid. All the extracts showed moderate cholinesterases inhibition, whereas methanol extracts exhibited highest urease inhibition and all extracts presented a relatively high inhibition against α-glucosidase. Similarly, all extracts showed strong to moderate cytotoxicity with IC50 values ranging from 53.02 to 382.7 μg/mL. Overall, results have suggested F. germanica to be a lead source for novel natural products. Highlights: First detailed biochemical and toxicological investigation was performed on methanol and dichloromethane extracts of Filago germanica aerial and root parts. High polyphenolic contents were observed in methanol extracts. Aerial and root methanol extracts were found to be most active with respect to antioxidant, enzyme inhibitions and cytotoxic activities.